1977
DOI: 10.1071/zo9770285
|View full text |Cite
|
Sign up to set email alerts
|

Adaptive behaviour of Drosophila adults in relation to temperature and humidity

Abstract: The reactions of three Drosophila species (D. melanogaster, D. simulans and D. immigrans) were studied in a temperature gradient at different humidities. In a saturation-deficit gradient all three species showed adaptive behaviour which could be related to their physiological resistance to desiccation. This is taken as experimental evidence for similar avoidance of stressful conditions in the field.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
21
0

Year Published

1978
1978
2019
2019

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(28 citation statements)
references
References 14 publications
3
21
0
Order By: Relevance
“…1). These survey data were in accord with a variety of laboratory experiments which consistently have suggested a higher fitness of D. melanogaster over D. simulans at high temperatures and vice versa (e.g., Prince & Parsons, 1977;Tantawy & Mallah, 1961;Tantawy & Soliman, 1967). However, whether the distributional differences between the sibling species in the field were indeed due to a greater temperature dependence of D. melanogaster needs further investigation.…”
Section: Species Numbers and Ratiosupporting
confidence: 70%
“…1). These survey data were in accord with a variety of laboratory experiments which consistently have suggested a higher fitness of D. melanogaster over D. simulans at high temperatures and vice versa (e.g., Prince & Parsons, 1977;Tantawy & Mallah, 1961;Tantawy & Soliman, 1967). However, whether the distributional differences between the sibling species in the field were indeed due to a greater temperature dependence of D. melanogaster needs further investigation.…”
Section: Species Numbers and Ratiosupporting
confidence: 70%
“…Here, the same synergetic-like phenomena was observed. Prince & Parsons (1977) showed that under low RH, D. melanogaster adults move towards lower temperatures likely to mitigate water loss. It is reasonable to speculate that in natural conditions, SWD adults also tend to avoid heat stress and low RH by searching for protected and favorable microhabitats, but this remains to be tested.…”
Section: Discussionmentioning
confidence: 99%
“…Humidity can have an overriding effect on position in a gradient (46). On the other hand, humidity may not affect temperature preference of well-hydrated animals (35, 69,216), but desiccated individuals often seek lower temperatures even at high humidity (69,193). The effect of acclimation temperature is variable.…”
Section: Thermal Preferencementioning
confidence: 97%
“…Many insects can be "trapped" by wandering into regions so cold that movement is inhibited, and often peaks of distribution appear in gradients fo r this reason (35), or apparent preference may shift downward over time (193). Preference distri butions often show a long tail on the cold side, contrasting with a very abrupt cut-off on the high side (35, 62,70).…”
Section: Thermal Preferencementioning
confidence: 99%